THE IMPLEMENTATION OF DIFFERENTIATED LEARNING STRATEGY FOR TEACHING SPEAKING IN MERDEKA CURRICULUM AT REMOTE ISLAND SARAPPO LOMPO: TEACHER’S VOICES - Wahdaniah Wahdaniah; Sultan Baa; Chairil Anwar Korompot (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aimed to finding out the teacher’ perceptions on the implementation of differentiated learning strategy for teaching Speaking in merdeka curriculum at remote island Sarappo Lompo. The research was conducted at SMP Negeri Satap 2 Liukang Tupabbiring and the research employed a qualitative case study design. Data were collected through interviews with one English teacher and classroom observations. The data analysis technique was conducted in three phases: data reduction, data display, and drawing conclusions. The results of this study showed the teacher demonstrated a comprehensive understanding of differentiated learning, emphasizing the importance of adapting instruction based on students’ readiness, interests, and learning profiles. In addition, the implementation was significantly constrained by various challenges. These included limited access to technological tools, a lack of authentic learning materials, time constraints in managing diverse student needs, and difficulties in maintaining equitable student engagement. Most notably, the geographical isolation contributed to a lack of ongoing professional development, which further hindered the teacher’ capacity to innovate and adapt instruction. The results suggest that teacher perception plays a crucial role in shaping effective differentiated instruction, especially in remote and under-resourced settings.